Prilagodljivi sistem za hlajenje orodij za brizganje plastike s pomočjo termoelektričnih modulov - Žagar, Boštjan (Strojniški vestnik, 2006)
One of the basic problems in the development and production process of moulds for injection moulding is the control of the temperature conditions in the mould. Nowadays, the temperature is controlled through a mould cooling system,which is composed of cooling channels, where the cooling fluid transports the needed heat to and from the mould. Such systems control the heat-exchange process throughout the entire mould, which is insufficient in many cases. For this reason it is necessary to develop a new system that will allow fast and precisely located temperature changes in defined mould locations. A precise study of the thermodynamic processes in moulds showed that heat exchange can be manipulated by thermoelectrical means. Such a systemupgrades conventional cooling systems within the mould or can be a stand-alone application for the heat manipulation within it. The upgraded system comprises the temperature-detection unit, the thermo-control unit and the final controlling element (thermo-element module as a heat pump), while the stand-alone unit needs an additional heat exchanger. These units form an adaptive closed loop. In this paper we present the results of a research project that was carried out in three phases, and its results are included in the A686\2006 patent. The testing stage, the prototype stage and the industrialisation phase will be presented. The main results of the project were the total and rapid online thermo-control of the mould over the cycle time and the overall influence on the quality of the plastic product, with an emphasis on deformation control. This system represents a milestone in the field of mould-temperature and product-quality control during the injection-moulding process.
Keywords: brizganje; polimeri; termodinamične lastnosti; orodja; hlajenje; termoelektrični členi